Pain and Aggression in Nursing Home Residents With Dementia. Issue 4 (July 2015) - Ahn, Hyochol; Garvan, Cynthia; Lyon, Debra
<x xml:space="preserve">Abstract</x> Background Few studies have examined the potential relationship between pain and aggressive behavioral symptoms in nursing home (NH) residents with dementia as a function of resident communicative status (ability to self-report pain). Objectives The objective of this study was to examine the relationship between pain and aggression for residents who self-reported pain and for those whose pain was measured by staff evaluation of pain-related behaviors. Methods This is a secondary analysis of the comprehensive data collected from January to March 2012 in the national Minimum Data Set (MDS) 3.0 of NH residents, aged 65 years or older, with dementia (N = 71, 227). Pain was measured using the MDS Pain Assessment Interview for residents who could communicate or by staff evaluation using the MDS Pain Behavior Scale for residents who could not communicate. The relationship between pain and aggressive behavioral symptoms was estimated from logistic regression models after controlling for covariates (functional/cognitive impairments, pain medications, comorbidities, and sociodemographic variables). Results In residents who could not communicate, pain was associated with both verbal and physical aggression (verbal aggression: adjusted odds ratio [AOR] = 1.23, 95% CI [1.17, 1.29]; physical aggression: AOR = 1.20, 95% CI [1.14, 1.26]). In residents who could communicate, pain was associated with verbal aggression only (AOR = 1.12, 95% CI [1.04, 1.18]). Discussion The relationship between pain and aggressive behavioral symptoms varies according to the communicative status of NH residents and disproportionately affects those who cannot articulate their pain. Strategies for enhancing pain management in these residents are needed to adequately treat pain and reduce aggression.